(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the development of value orientations in primary school children as a key area of modern education. It explores the concept of "value orientations," their role in the development of a child’s personality, and their influence on behavior, relationships, and academic performance. Particular attention is paid to the psychological and pedagogical conditions for value formation in primary school, as well as the role of family, school, and teacher in this process. The article analyzes the main areas of educational work that contribute to the development of moral, social, cultural, and academic values in primary school students. The article concludes that targeted pedagogical work to develop value orientations contributes to the harmonious development of a child’s personality and their successful socialization.